Estimation of the surface ablation and mass balance of Eustre Grønfjordbreen (Spitsbergen) - R. A. Chernov; A. V. Kudikov; T. V. Vshivtseva; N. I. Osokin (Лëд и снег, 2019)
Due to climatic changes in Spitsbergen the glaciation of the Nordenskjold Land (West Spitsbergen) has significantly degraded over the past 100 years. Changes in glaciers are undoubtedly associated with intensive melting caused by a rise of summer air temperatures. Based on the results of field measurements of ablation on the East Grenford glacier, data on the ice reduction were obtained since 2004. Analysis of the results showed that magnitude of the surface ablation is in a good agreement with the values calculated by the Krenke–Hodakov formula, in which the argument is the average summer air temperature. The parabolic dependence of the Krenke-Hodakov formula with the exponent of 3.25 presented the best approximation to the field measurements for all high-altitude zones of the glacier with a correlation coefficient of 0.96. The calculated values of ablation of ice and snow were used to estimate the mass balance of the East Grenford glacier since 2004. The calculations were based on the following: measured values of jump in temperature at the boundary of the glacier, averaged values of the air temperature gradient, and averaged data on snow storage on the glacier. Data on the mass balance of the glacier is indicative of its shortening during the last decade, despite the interannual variations. In 2016, the glacier mass balance reached the lowest value equal to −1990 mm, the calculated value was equal to −1960 mm. Analysis of the data demonstrated that the average summer air temperature is the major factor affecting the glacier mass balance. These results may be useful for estimating  melting and mass balance of a number of mountain glaciers of the Nordenskjold Land.